Cytoskeleton in specialized tissues and in pathological states : a multi-volume treatise - Hesketh, John E.; Pryme, Ian F. (Cytoskeleton, 1996)
This volume deals with aspects of the cytoskeleton in different cell types and also describe examples of changes in the cytoskeleton which occur during various pathological states. These studies bring the exciting area of cytoskeleton research into the domain of medical science.